Audiovisual verification in the evolution of television newsrooms : Al Jazeera and the transition from satellite to the cloud - Bañon Castellón, Lola (Anàlisi, 2021)
With the spread of the digital sphere and the proliferation of images from indirect sources that can be accessed by systems and users, verification routines have become essential to ensure media corporations’ credibility. The advances in artificial intelligence which allow automated fact-checking (AFC) initiatives to be created help detect falsehoods, but they do not eliminate the need for human intervention. On the contrary, information professionals are necessary, and their functions increasingly include procedures such as mediating in videos and images. This study analyses the evolution of verification routines in audiovisual journalism and how new techniques have influenced the perception of trustworthiness and the reorganization of the television newsroom by allowing content from outside the media’s own newsroom. To do so, it combines a method that examines the main literature on verification processes and compares it with the procedure used by Al Jazeera. In this regard, an exploration was conducted out based on participant observation in this international TV channel via interaction with journalists and heads of the corporation. The results indicate that advances in verification procedures make it possible to introduce visual material from the social media into the corporation’s common news topics contributing to the transition from the traditional newsroom to the cloud structure and the inclusion of new audiences. These changes affect journalistic routines in a profession which has no longer been in-person for some time, in which correspondents coexist with journalists working in virtual mobility, seeking and receiving images in and from the social media.